The Child’s Experience of Relatives with Mental Health Problems: How Can Middle Grade Authors Combat Stigma? - Hannah Durkan (Leaf Journal, 2025)
The effects of the stigmatisation of people with mental health problems (MHPs) should not be underestimated; stigma becomes a barrier to seeking help and can lead to feelings of shame, fear and isolation for children within the family. Through the examination of three Middle Grade (MG) depictions of relatives with MHPs – The Rollercoaster Boy by Lisa Thompson, The Tiger who Sleeps Under My Chair by Hannah Foley and Boy in The Tower by Polly Ho-Yen – this article will investigate how MG authors can portray characters with MHPs realistically, compassionately and with the aim to combat stigma. I suggest that using metaphors to describe MHPs can both aid understanding for children and provide a clear separation between the person and their symptoms, thus reducing blame. When stories acknowledge the experience of stigma and confront it directly with empathetic characters who hold alternative viewpoints, the negative stereotypes which young readers are likely to encounter in their lives are directly challenged. I discuss why MHPs must be normalised by providing a wide-range of characters across the MG reading experience. MHPs are common, can affect anyone and are often invisible. In truth, they are simply part of being human.